TIME LIMIT, GEOCHEMICAL CHARACTERISTICS AND TECTONIC SETTING OF LATE PALEOZOIC MAGMATISM IN SAWUER REGION, XINJIANG - Zhou T.F.; Yuan F.; Tan L.G.; Fan Y.; Yue S.C.; Yang W.P.; He L.X. (My University, 2006)
Sawuer region is located in west Junggar, Jimunai County of Altay district and Hefeng county of Tacheng district, Xinjiang province. The region is along the north margin of Kazakstan-Junggar plate. The post-collisional magma of late Paleozoic are widespread. The intrusions formed from 328.2Ma to 290.7Ma (from late Carboniferous to early Permian), the volcanic rocks in Haerjiawu Group and Kalagang Group formed from 296.7Ma to 280Ma (early Permian). The geochemical evolvement characteristics of the intrusions from early to late (Sentasi intrusion, Wokensala intrusion → Tasite intrusion → Kaerjia intrusion → Kuoyitasi intrusion, Qiaqihai intrusion) are obviously. The volcanic rocks in Haerjiawu Group have weak bimodal characteristics and those in Kalagang Group have typical bimodal characteristics, indicating that they formed in extension setting. Based on the time frame, geochemical evolvement characteristics and tectonic setting of the late Paleozoic magma, we think that the Sawuer region was in post-collisional setting from late Carboniferous to early Permian, and the setting evolved from extrusion-extension translation stage to extension stage gradually.
Keywords: GEOCHEMICAL; GRANITE; POST-COLLISIONAL; SAWUER REGION; VOLCANIC ROCKS; XINJIANG; Палеозой::Пермская; Палеозой::Каменноугольная; Paleozoic::Permian; Paleozoic::Carboniferous